Nanotechnology-based Drug Delivery Systems for Dermatomycosis Treatment - Ribeiro de Souza, Ana Luiza [UNESP]; Kiill, Charlene Priscila [UNESP]; dos Santos, Fernanda Kolenyak [UNESP]; da Luz, Gabriela Marielli [UNESP]; Rocha e Silva, Hilris [UNESP]; Chorilli, Marlus [UNESP]; Gremião, Maria Palmira Daflon [UNESP] (Bentham Science Publ Ltd, 2012)
Dermatomycosis are fungal infections that involve the stratum corneum of the skin and the nails, hair, and surfaces of mucous membranes. Mycological infections represent important public health disorders, and their incidence has increased in recent years. This increase may result from a number of causes, such as an increase in the susceptible population, including the elderly and immunodeficient, and social and cultural exchanges associated with sports and the use of swimming pools. In immunodeficient individuals, the lesions associated with dermatomycosis are more intense, and what are initially superficial lesions can result in disseminated and fatal forms. The primary reasons for this include antifungal resistance, toxicity, lack of rapid and specific diagnoses and the poor penetration of drugs. The currently available antifungal agents for the treatment of dermatomycosis include azole and the allylamine group of drugs. The problems related to dermatomycosis therapy are the low residence times of the dosage forms in the site of action, side effects and variable drug permeability. Thus, novel topical drug delivery systems for antifungal therapy have been developed, including liposomes, niosomes, solid lipid nanoparticles, nanostructured lipid carriers, silver nanoparticles, microemulsion and liquid crystals. The objective of this study is to present a systematic review of nanotechnology-based drug delivery systems for dermatomycosis treatment.
Keywords: Dermatomycosis; drug delivery systems; nanotechnology